Multi-objective approach for load shedding based on voltage stability index consideration - R. Kanimozhi; K. Selvi; K.M. Balaji (Alexandria Engineering Journal, 2014)
In voltage stability analysis, it is useful to assess voltage stability of power systems by means of scalar magnitudes, or indices. Operators can use voltage stability indices to know how close the system to voltage collapse. The voltage stability indices are a powerful tool to identify the weakest bus and critical line. This identification can be used to gain control over devices for voltage stability up to certain level and load shedding is possible if the load keeps on increasing. This paper presents a computationally simple index based load shedding algorithm using weighted sum genetic algorithm where an AC power flow solution cannot be found for the stressed conditions. Minimization of total load shed and sum of New Voltage Stability Index (NVSI) at the selected buses are considered as two objectives of this algorithm to restore the power flow solvability. This is validated in both IEEE 30 bus system and a practical system Tamil Nadu Electricity board (TNEB) 69 bus system in India for considering both heavy loading and (N − 1) contingency.